2003
DOI: 10.1177/030802260306600704
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Play and Leisure in Junior School Aged Children with Juvenile Idiopathic Arthritis: What are the Implications for Occupational Therapy?

Abstract: Play is the dominant occupation in childhood and is recognised as having an important role in wellbeing. Past research suggests that children with a disability experience a variety of barriers to engagement in play. Despite this, play is often not assessed as a specific area of occupational performance. This qualitative study aimed to explore the perceptions of play and leisure in junior school aged children with juvenile idiopathic arthritis. Twelve children between the ages of 7 years and 11 years were inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 24 publications
4
34
0
Order By: Relevance
“…Three studies included females only . The ages of participants ranged from 6 to 21 years: four studies focused exclusively on 6‐ to 12‐year‐olds, four focused on 13‐ to 19‐year‐olds, and all other studies included both age groups …”
Section: Resultsmentioning
confidence: 99%
“…Three studies included females only . The ages of participants ranged from 6 to 21 years: four studies focused exclusively on 6‐ to 12‐year‐olds, four focused on 13‐ to 19‐year‐olds, and all other studies included both age groups …”
Section: Resultsmentioning
confidence: 99%
“…A coding scheme was developed iteratively and collaboratively, similar to an approach used by Hackett 14 and following guidelines for coding and analysis outlined by Taylor and Bodkin, 15 to code the reflective journals.…”
Section: Analytic Frameworkmentioning
confidence: 99%
“…The importance of leisure among patients in community was identified, yet only a few of them were qualitative studies (Hodgson et al. 2001, Hackett 2003, Pereira & Stagnitti 2008, O’Sullivan & Chard 2010). The leisure studies in Hong Kong are rare, and they only revealed the discrepancy between patients’ needs for leisure and their actual participation, without exploring the reasons.…”
Section: Introductionmentioning
confidence: 99%